What is the role of corporate governance as a sub-species of corporate law in the level of corporate risk taking? - Becker, Cleo (Department of Commercial Law, 2014)
The Aim of this paper is to highlight the possible causes of the current global financial crisis; both legal and regulatory, and to examine how corporate governance, as a sub-species of corporate law can be used to curb excessive risk taking. This paper will examine the failure of current corporate law and regulation to curb excessive risk taking behaviour and present proposals for reform of the existing system. This necessitates comparison between South Africa, the U.S.A (particularly the State of Delaware) and the United Kingdom, where the crisis has lead to recent legislative and regulatory reforms.